Current influences and approaches to promote future physical activity in 11–13 year olds: a focus group study. (December 2015) - Carlin, Angela; Murphy, Marie; Gallagher, Alison
Abstract Background Many children and adolescents are failing to meet current physical activity (PA) guidelines and consequently not achieving the benefits associated with regular participation in PA, with girls consistently less active than boys. In order to design interventions to increase physical activity in adolescents it is important to understand their perceptions of and preferences for physical activity. Methods One hundred eighty participants, mean (SD) age 12.1 (0.5) years, completed the Physical Activity Questionnaire for Children (PAQ-C) and had height and weight measured. This information was used to select a subsample of participants (n64; mean (SD) age 12.3 (0.4) years; 39 females; 25 males; 25 % overweight/obese) to take part in focus group discussions. Participants were grouped based on PAQ-C responses into 'low-active' and 'highly-active' groups, so that those with similar existing levels of PA were in the same focus group. A semi-structured discussion guide was employed to explore the key influences on current PA participation and to actively seek ideas on how best to promote future PA in this population. In total, nine focus groups (mixed-gender) were conducted within the school setting. All focus groups were audio recorded, transcribed verbatim and analysed thematically. Results A number of themes emerged in relation to influences on current PA including friendship and peers, family and other people, the consequences of not taking part in PA, changing priorities, and cost and access to resources. With regards to the future provision of PA, participants favoured opportunities to try new activities, increased provision of school-based activities which can be undertaken with friends and activities which incorporated the use of technology and encouragement through rewards and incentives. Gender differences were apparent in relation to the types of activities participants preferred taking part in. Differences were also observed between 'low-active' and 'highly-active' groups in relation to barriers to current participation in PA. Conclusions This study has highlighted a number of influences on current and future participation in PA, which differed based on gender and existing PA levels, for example, maximising the potential of the school day and including technology and incentives. These components can inform targeted interventions to increase PA in low active adolescents.